Communication Strategies for Climate Change Disaster Mitigation in Kota Lama Semarang - Setiawan, Deddy; Mihardja, Eli Jamilah (JURNAL SOSIAL HUMANIORA (JSH), 2024)
Kota Lama Semarang, rich in cultural and architectural heritage, is vulnerable to disasters like Rob Floods and rising sea levels due to climate change. This research aims to describe recommended communication strategies for increasing awareness and community involvement in climate change disaster mitigation. Through analysis of the news text, data analysis, and literature review, this study provides valuable insights for stakeholders. The communication strategy utilizes storytelling through social media, awareness campaigns, and educational programs. Effective communication is crucial in facing disasters in Kota Lama Semarang. The recommended strategy emphasizes community-based approaches with active participation. Dialogues with the government, NGOs, and relevant institutions strengthen community adaptation. Challenges include accessibility and technology limitations in the area. Cultural and linguistic diversity should be considered in communication strategies to enhance message reception. Ongoing evaluations are necessary to enhance communication strategy effectiveness. In conclusion, effective communication strategies are vital in addressing climate change disasters in the Kota Lama Semarang. This strategy promotes community awareness, involvement, and adaptation. Challenges such as technology accessibility and cultural diversity should be wisely managed. By overcoming these challenges and conducting continuous evaluations, communication strategies can reduce disaster risks and build community resilience.